Positioning in an Inter-Professional Team Meeting: Examining Positioning Theory as a Methodological Tool for Micro-Cultural Group Studies - Hirvonen, Pasi (Qualitative Sociology Review, 2013)
This paper sets out to test the possibilities of the Positioning Theory as a means to approach small group phenomena from a micro-cultural perspective. The study draws on a transcription of a videotaped inter-professional team meeting in the field of social services. Analysis of the data was set to examine how the basic concepts of the Positioning Theory suit the analysis of in-group phenomena, what different forms of positioning are present, and how the positioning is connected to the group processes. Studying the group’s interaction shows how it is possible to approach the interaction via the basic concepts of the Positioning Theory and how the positioning is intervened with group processes, such as decision-making, arguing, and conflict. The study also offers a new theoretical and empirical perspective to the research on small group dynamics.